2012
DOI: 10.1212/wnl.0b013e3182752ea8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as a protective factor in multiple sclerosis

Abstract: This study supports the presence of an association between high 25(OH)D levels during the years preceding disease onset and a decreased risk of MS. In the very limited material with samples drawn in early pregnancy, where month-of-birth effects were controlled for, we found no association between gestational 25(OH)D levels and MS risk in the offspring. Decreasing 25(OH)D levels in the population may contribute to explain the increasing MS incidence that is suggested from epidemiologic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
3
14

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(191 citation statements)
references
References 29 publications
8
166
3
14
Order By: Relevance
“…A longitudinal study evaluated serum vitamin D levels derived from blood samples of seven million US military personnel [85]. Those with 25(OH)D levels superior to 40 ng/mL had a 62% lower chance of developing MS. A more recent prospective study confirmed these findings and reported that levels of vitamin D over 30 ng/mL were associated with a decreased MS risk [86]. Adiposity has been associated with lower vitamin D levels [87][88], and higher body mass index (BMI) has been associated with higher incidence of MS in adolescent women, but not in adult women [89].…”
Section: Vitamin D Deficiency and Multiple Sclerosis: Role In The Susmentioning
confidence: 82%
“…A longitudinal study evaluated serum vitamin D levels derived from blood samples of seven million US military personnel [85]. Those with 25(OH)D levels superior to 40 ng/mL had a 62% lower chance of developing MS. A more recent prospective study confirmed these findings and reported that levels of vitamin D over 30 ng/mL were associated with a decreased MS risk [86]. Adiposity has been associated with lower vitamin D levels [87][88], and higher body mass index (BMI) has been associated with higher incidence of MS in adolescent women, but not in adult women [89].…”
Section: Vitamin D Deficiency and Multiple Sclerosis: Role In The Susmentioning
confidence: 82%
“…Se han descrito otros factores asociados como la concentración de vitamina D y la exposición al sol, con reducción de la susceptibilidad al incremento de los niveles séricos de vitamina D. El tabaquismo, en el contexto de ciertos genes de HLA, tiene una fuerte influencia negativa en la susceptibilidad. 7,8,9,10 Respuesta inmune en EM: componentes de la respuesta inmunológica innata y adaptativa En el centro de la respuesta inmune de la EM se encuentra el componente células T CD4+. En el SNC están las células inmunes más importantes, las microglías, células propias de la respuesta inmune innata, sumamente sensibles a cambios y capaces de secretar mediadores solubles y presentar antígenos; sus procesos apendiculares se extienden lejos del cuerpo celular, disposición que les permite detectar cambios menores de las células adyacentes, como las neuronas y los astrocitos.…”
Section: Antecedentesunclassified
“…According to the results of our study, VitD deficiency influences greater percent of disability burden among MS patients. Many studies reported a negative correlation between serum VitD levels and disability [13][14][15][16][17].…”
Section: Disabilitymentioning
confidence: 99%